Analisa Prediksi Jumlah Pembuatan Roti Menggunakan Penerapan Metode Fuzzy Inference System Dengan Algoritma Tsukamoto - Munawaroh Munawaroh (Politeknik Harapan Bersama, 2018)
The number of unsold bread causes PT Seru Bakery to suffer a loss. This is based on the absence of a system that regulates the making of bread on PT.Seru Bakery, so that the making of bread refers only to the wishes of the author alone. In PT exciting Bakery there are 2 Size of bread and each - each type consists of 3 flavors. For small bread is priced Rp.1000 and has a taste of chocolate, cheese and coconut, for a large bread that sells for Rp.2000 that is mocha, pia and fried chocolate. This research use method of fuzzy tsukamoto inference system using 3 variable that is, demand, inventory, and production, application of method of fuzzy tsukamoto in making planning to determine amount of production expected to increase profit where maximum production obtained from maximal sale and at least reduce amount the number of returns in the previous few months, if the lowest demand is 661 brown bread/day and highest The highest demand is 922 brown bread / last request problem = 735 chocolate flavour bread, as well as the lowest supply, is 278 chocolate flavour bread / day, highest supply is 643 chocolate flavour bread/day and Supply problems = 635 chocolate flavour bread, then the bread produced is as much as 1284 bread, the difference between manual calculation and the system of 86 pieces of bread. So with the FIS method Tsukamoto can suppress losses of 86 pieces of bread.